Micropatterned Cell‐Repellent Interface Using Femtosecond Laser Direct Writing to Engineer Controlled Cell Organization. Issue 7 (4th June 2021) - Yang, Wenguang; Chu, Honghui; Cai, Shuxiang; Liang, Wenfeng; Yu, Haibo; Wang, Yuechao; Liu, Lianqing
Abstract: Cell‐repellent interfaces have various applications, including microfluidic devices, biosensors, and antibiofouling surfaces. Efficient cell repellency, long‐term stability, and ability to fabricate micropatterns with cell repellency are main optimal requirements for cell‐repellent interfaces. In this study, a flexible and practical method is proposed to construct a cell‐repellent interface and engineer controlled cell organization. Using femtosecond‐laser direct writing to pattern surfaces with microcraters, it is shown that micropatterned surfaces with physical and chemical changes have outstanding characteristics of super‐hydrophobicity. Furthermore, the cell adhesion is inhibited by these features and arbitrary cell patterns are achieved by selective cell adhesion induced by the distribution of the microcrater structures. These findings suggest a high potential for directing cell organization with desired shapes to analyze the fundamental mechanism of cell adhesion. Abstract : Herein, a flexible and practical method to construct cell‐repellent interfaces and engineer controlled cell organization is investigated. Microcraters patterns have been rapidly fabricated using femtosecond laser direct writing, and shown outstanding superhydrophobicity. Furthermore, cell adhesion is inhibited by the features and arbitrary cell patterns are achieved by selective cell adhesion induced by distribution of microcraters structures.